Naser Dumairieh. Intellectual Life in the Ḥijāz before Wahhabism Ibrāhīm al-Kūrānī’s (d. 1101/1690) Theology of Sufism - AKBULUT, DİDAR AYŞE (My University, 2024)
The post-classical Islamic intellectual history has garnered increased attention in recent decades. While most of the works from the period, often summarily dismissed as unoriginal commentaries and glosses, are tucked away in manuscript libraries, there are scholars undertaking the formidable task of exploring these almost obscure works and their authors. Naser Dumairieh’s book stands as a valuable addition to this literature. By taking Ibrāhīm al-Kūrānī in center, Dumairieh not only presents a cohesive overview of some of the most acute theological and intellectual debates of the seventeenth century but also highlights the importance of the Hijaz, and its centrality and complexity in global Islamic intellectual history well before the rise of Wahhabism and other reformist movements in the eighteenth century.
Keywords: Sosyal ve Beşeri Bilimler; Tarih; Social Sciences and Humanities; History; Sanat Ve Beşeri Bilimler (Ahci); Sosyal Bilimler (Soc); Sanat Ve Beşeri Bilimler; Arts & Humanities (Ahci); Social Sciences (Soc); Arts & Humanities; Sosyal Bilimler ve Beşeri Bilimler; Social Sciences & Humanities